Hospital Tariff Setting, Patient Experience, and Patient Satisfaction under New Public Management Reforms: A Systematic Review - I Gusti Agung Ayu Eka Mahastuti; Agus Fredy Maradona; Adhar Arifuddin (Journal of Health and Nutrition Research, 2026)
Public hospitals are under sustained pressure to reconcile fiscal sustainability, service quality, and equitable access. New Public Management (NPM) reforms influence tariff setting by expanding managerial autonomy, output-based financing, performance measurement, and market-like incentives. This review aims to synthesize evidence on how NPM-oriented hospital tariff and provider-payment policies influence patient experience and patient satisfaction in public hospitals. Methods: A systematic review was conducted according to PRISMA 2020. Scopus, Web of Science, PubMed/MEDLINE, ScienceDirect, and SAGE Journals were searched for English-language literature published from January 2019 to June 2026, while seminal older works were retained for theoretical framing. After duplicate removal and screening, 45 sources were included in thematic synthesis, comprising 31 primary empirical studies, 8 review articles, and 6 conceptual or policy analyses. Tariff and payment reforms may improve cost control, technical efficiency, and managerial responsiveness, but the included literature also links poorly calibrated tariffs with cost shifting, service selection, shortened length of stay, coding pressure, and distrust when payment rules are opaque or misaligned with actual service costs. Patient experience described what patients actually encountered during care, including access, waiting, communication, billing clarity, and affordability, whereas patient satisfaction reflected evaluative judgment against expectations and perceived value. Hospital tariff reform is a governance intervention rather than a purely technical pricing exercise. Sustainable reform requires periodic cost review, quality-sensitive payment design, transparent patient-facing communication, and safeguards for equity.